1999
DOI: 10.1128/jvi.73.7.5945-5956.1999
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Peptides with Sequences from the Newcastle Disease Virus Fusion Protein Heptad Repeat Regions

Abstract: Typical of many viral fusion proteins, the sequence of the Newcastle disease virus (NDV) fusion protein has several heptad repeat regions. One, HR1, is located just carboxyl terminal to the fusion peptide, while the other, HR2, is located adjacent to the transmembrane domain. The structure and function of a synthetic peptide with a sequence from the region of the NDV HR1 region (amino acids 150 to 173) were characterized. The peptide inhibited fusion with a half-maximal concentration of approximately 2 μM; how… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
36
2

Year Published

2000
2000
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(40 citation statements)
references
References 50 publications
2
36
2
Order By: Relevance
“…Recently, it has been shown that both the Nterminal and the C-terminal heptad repeats of the Sendai virus fusion protein, which form a strong complex in solution (Ghosh et al, 1998), dissociate into a-helical monomers upon binding to membranes (Ben-Efraim et al, 1999). In agreement with these observations, NMR studies showed that the N-terminal heptad repeat of the homologous Newcastle disease virus fusion protein has an a-helical structure in SDS, consistent with the notion that it binds parallel with the bilayer, as a monomer, with its hydrophobic face buried in the membrane (Young et al, 1999). Furthermore, the N-terminal heptad repeat of the Sendai virus F1 protein, located between the N-terminal fusion peptide and SV-208, has been shown to assist the N-terminal fusion peptide in inducing membrane fusion (Ghosh & Shai, 1999).…”
Section: Sv-208 Has Characteristics Similar To Other Known Fusion Pepsupporting
confidence: 67%
“…Recently, it has been shown that both the Nterminal and the C-terminal heptad repeats of the Sendai virus fusion protein, which form a strong complex in solution (Ghosh et al, 1998), dissociate into a-helical monomers upon binding to membranes (Ben-Efraim et al, 1999). In agreement with these observations, NMR studies showed that the N-terminal heptad repeat of the homologous Newcastle disease virus fusion protein has an a-helical structure in SDS, consistent with the notion that it binds parallel with the bilayer, as a monomer, with its hydrophobic face buried in the membrane (Young et al, 1999). Furthermore, the N-terminal heptad repeat of the Sendai virus F1 protein, located between the N-terminal fusion peptide and SV-208, has been shown to assist the N-terminal fusion peptide in inducing membrane fusion (Ghosh & Shai, 1999).…”
Section: Sv-208 Has Characteristics Similar To Other Known Fusion Pepsupporting
confidence: 67%
“…Monolayers of cells were infected with 1 moi of NDV for 1 h at 37°C. At 7 h post-infection, viral F proteins were activated by digestion with acetyl trypsin [33]. Then, cells were incubated in complete medium overnight and stained with Giemsa or crystal violet for syncytium observation.…”
Section: Syncytium Assaysmentioning
confidence: 99%
“…For example, analogs of the orthomyxovirus, paramyxovirus (Richardson et al, 1980) and HIV-1 fusion peptide domains (Gallaher et al, 1992;Owens et al, 1990;Silburn et al, 1998) block viral infection, presumably by forming inactive heteroaggregates. Likewise, peptides analogous to the HR regions of the HIV-1 (Gallaher et al, 1992;Qureshi et al, 1990;Wild et al, 1992Wild et al, , 1993, paramyxovirus (Lambert et al, 1996;Young et al, 1999) or Ebola virus (EboV) (Watanabe et al, 2000) class I viral fusion proteins block virion infectivity by preventing the transition of the fusion protein into the six-helix bundle state. The anti-HIV-1 peptidic drug Fuzeon TM (DP178, T-20 or enfuvirtide), which overlaps HR2 and the aromatic domain of gp41, was the first of a new class of fusion inhibitor antivirals to gain FDA approval (2003).…”
Section: Introductionmentioning
confidence: 99%